Mapping the Incidence of Radiation from the Microwave Oven by the Texture of Cheese Breads (Pães de Queijo) - Bianchini, Giulia Silva; Andrade, Luan Alberto; Pereira, Joelma (Food Science and Engineering, 2024)
Food heating in microwave ovens is fast but not uniform. To understand the temperature distribution in these ovens, it is necessary to know the operation of the oven and the interaction of microwaves with the food, in this case, cheese bread. Cheese bread (Pão de queijo) is a traditional Brazilian bread widely sold and consumed throughout Brazil. This study aimed to map the incidence of radiation in the domestic microwave oven by evaluating the texture of cheese breads, depending on their formulation and location on the plate during baking. The three formulations used were a control, one with a higher amount of milk, and another with a higher amount of cheese. The response variable evaluated was texture, using a texturometer. The texture of cheese bread was measured by compressive strength analysis using the Stable Micro Systems texture analyzer equipment. All tests were carried out after cooling the cheese breads for 20 minutes after baking, and in triplicate. An analysis of variance of the texture was applied to test the treatments, position on the microwave plate (nine levels), and composition of the cheese bread (three levels), and the means were compared by Tukey's test (95% confidence). The microwave distribution was not uniform in the control and in the formulation with a higher quantity of milk. The lack of uniformity in the distribution of radiation caused by the position of the cheese bread on the microwave oven plate occurs because of cold spots and hot spots in specific places in the oven during operation. In conclusion, the incidence of radiation in the domestic microwave oven during the baking of cheese bread is a function of its formulation and location during baking.